Principles of integrated marketing communications : an eEvidence-based approach - Ang, Lawrence (Cambridge University Press, 2021)
Marketing in the digital age poses major challenges for traditional and established practices of communication. To help readers meet these challenges Principles of Integrated Marketing Communications: An Evidence-based Approach provides a comprehensive foundation to the principles and practices of integrated marketing communications (IMC). It examines a variety of traditional and digital channels used by professionals to create wide-reaching and effective campaigns that are adapted for the aims of their organisations. This edition has been thoroughly revised and each chapter includes: case studies of significant and award-winning campaigns from both Australian and international brands that illustrate the application of explored concepts; discussion and case study questions that enable readers to critically evaluate concepts and campaigns; a managerial application section that illustrates how concepts can be applied effectively in a real situation; a 'further thinking' section that expands knowledge of advanced concepts and challenges readers to think more broadly about IMC.